Highly sensitive and miniaturized microcone-curved resonant photoacoustic cavity for trace gas detection - Zhongke Zhao; Wenjun Ni; Chunyong Yang; Sixiang Ran; Bingze He; Ruiming Wu; Ping Lu; Perry Ping Shum (Photoacoustics)
This paper proposes a novel microcone-curved resonant photoacoustic cell (MCR-PAC) for highly sensitive trace gas detection. The MCR-PAC features with microcone-curved resonant region and cylindrical buffer chamber, which dominates the photoacoustic signal amplification. By introducing the hyperbolic eccentricity as a new optimization dimension, the quality factor of the MCR-PAC is remarkably strengthened to enhance the acoustic pressure amplitude. At an eccentricity value of 5, the volume of the photoacoustic resonant cavity is approximately 0.23 cm3. Targeting trace acetylene, the system achieves a minimum detection limit of 1.41 ppb with an integration time of 290 s, corresponding normalized noise equivalent absorption coefficient is 1.88×10−9 W·cm−1·Hz−1/2. Compared to the traditional T-type PAC, the overall performance of MCR-PAC has been enhanced nearly fourfold. With its compact millimeter-scale dimensions and high sensitivity, the MCR-PAC demonstrates extensive potential for application in environmental monitoring and breath diagnostics.